Clinically suspected myocarditis complicating dengue shock syndrome: a case report and literature review of cardiac complication in dengue-affected pediatric patient - Dita Aulia Rachmi; Drastis Mahardiana; Eka Prasetya Budi Mulia; Agus Subagjo (Zaslavsky O.Yu., 2021)
We report a case of dengue shock syndrome complicated by clinically suspected acute myocarditis in pediatric patient at a limited-resources hospital in a rural area and review the literature. A 12-year-old boy who experienced dengue shock syndrome developed bradycardia on day 7th of illness. His electrocardiogram during the bradycardia showed sinus bradycardia with a rate of 50 beats per minute. Atropine sulfate and dobutamine, alongside supportive management, were administered. The patient recovered 4 days later. We found a total of seven articles involving pediatric patient with dengue illness and cardiac complications by PubMed search. Clinical manifestations of cardiac involvement in pediatric patient with dengue varied and were mostly transient from tachy-bradyarrhythmia, sinus node dysfunction, low blood pressure, decreased ejection fraction, lower cardiac output, and increased cardiac enzyme. Transient cardiac abnormality can be an important presentation, and physician should have high awareness of cardiac complication in dengue-affected pediatric patients to manage them accordingly.